In vitro activity of vancomycin, quinupristin/dalfopristin, and linezolid against intact and disrupted biofilms of staphylococci - Kanchanapoom Termkiat; Rao Suma; El-Azizi Mohamed; Khardori Nancy (BMC, 2005)
Abstract Shed cells or disrupted parts of the biofilm may enter the circulation causing serious and very hard to treat biofilm-associated infections. The activity of antimicrobial agents against the shed cells/disrupted biofilms is largely unknown. Methods We studied the in vitro susceptibility of intact and disrupted biofilms of thirty clinical isolates of methicillin-resistant and methicillin-susceptible Staphylococcus aureus (MRSA and MSSA) and Staphylococcus epidermidis to vancomycin, quinupristin/dalfopristin, and linezolid and compared it to that of the suspended (planktonic) cells. Results Bacteria in the disrupted biofilms were as resistant as those in the intact biofilms at the minimum inhibitory concentrations of the antibiotics. At higher concentrations, bacteria in the disrupted biofilms were significantly (P < 0.001) less resistant than those in the intact biofilms but more resistant than the planktonic cells. Quinupristin/dalfopristin showed the best activity against cells of the disrupted biofilms at concentrations above MICs and vancomycin, at 500 and 1,000 μg/ml, was significantly more active against the biofilms of MRSA and S. epidermidis Conclusion The difficulty of treating biofilm-associated infections may be attributed not only to the difficulty of eradicating the biofilm focus but also to the lack of susceptibility of cells disrupted from the biofilm to antimicrobial agents.